Commentary: Alpha-synuclein interacts with SOD1 and promotes its oligomerization - Helferich, Anika Marie; McLean, Pamela J.; Weishaupt, Jochen H.; Danzer, Karin M. (Journal of neurology & neuromedicine, 2016)
Alpha-synuclein and Cu, Zn superoxide dismutase (SOD1) are both aggregation-prone proteins that are associated with Parkinson’s disease (PD) and amyotrophic lateral sclerosis (ALS), respectively. Recently, we showed that alpha-synuclein interacts with SOD1 in various cell types and tissues. Using a cell culture model, we also found that alpha-synuclein nucleates the polymerization of SOD1. Here, we discuss the current literature regarding their interaction and their co-localization in aggregates of human post-mortem tissue. Furthermore we comment on the reported alpha-synuclein-induced SOD1 polymerization in terms of cross-seeding effects in neurodegeneration.